Alkali and silane treatments towards exemplary mechanical properties of kenaf and pineapple leaf fibre-reinforced composites - Dhar Malingam, Sivakumar; Ng, Lin Feng; Razali, Nadlene; Subramonian, Sivarao (Springer, 2020)
Following the contemporary research trend of exploring the potential of eco-friendly natural fibres, this work studies the effects of alkali and silane treatments, with varying concentrations, on the mechanical characterization of composites reinforced with kenaf and pineapple leaf fibre (PALF). Kenaf- and PALF-based composites were fabricated through the heat compression method. Their mechanical characterization was then performed to evaluate the tensile, flexural and impact properties. The findings concluded that chemical treatments indeed enhanced the mechanical properties of composite materials. 5% NaOH and 3% silane treatments can respectively provide the optimum mechanical properties to the kenaf fibre and PALF reinforced composites. Chemical treatment results evidenced that silane-treated composites exhibit higher mechanical properties compared to the NaOH-treated composites. When comparing the mechanical properties of kenaf- and PALF-reinforced polypropylene composites, the overall results show that composites based on PALF have superior mechanical properties